Challenges of Former Seminarian Students and Their Coping Strategies - Jezunlu N. Lim; Jirold A. Lucmayan; Evan P. Taja-on (PT FORMOSA CENDEKIA GLOBAL, 2023)
Seminary provides rigorous study, reflection, and spiritual growth for seminarians. Seminary is perfect for continuing to discern God's purpose through study, prayer, and community. However, leaving a close-knit community is hard for seminarians, who leave for different reasons. The study is grounded in the existing literature on the topic, suggesting that more comprehensive and up-to-date data on the challenges former seminarian students face in higher education is needed. The study addressed a gap in understanding former seminarians' problems. The study used a descriptive research design with an exploratory case study design, employing a survey method to gather the data needed for the study. The study uncovered that the former seminarians face financial and personal challenges. The study discovered that the former seminarians coping strategies to overcome challenges fall within the scope of six intrinsic and two extrinsic strategies.